PENGARUH PROFITABILITAS TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018) - Kamarullah, Ririn Ismira Afiyani; Bailusy, Muhsin N; Hadady, Hartaty (Jurnal MS, 2022)
Objective: This study aims to determine the effect of ROA, ROE, EPS and NPM variables on stock returns (Y) partially and simultaneously. The research sample is 45 companies. The data collection technique is done by the documentation method, which is collecting data in the form of book literature, journals, and the company's annual financial statements. The data needed in this study is secondary data from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The financial statements were downloaded from the site www.idx.co.id. Methodology: The analytical method used in this study is the Panel data regression method as analysis technique used is quantitative. Finding: ROA (H1), ROE (H2), EPS (H3) are accepted (positive affect), while H4 (NPM) are accepted (positive affect) at the 5% confidence level. Conclusion: The results showed that ROA has a positive and significant effect on stock returns, the more effective the users of the company's assets, then by itself efforts to increase profits can be maximally generated and ultimately can increase the value of stock returns. ROE has a positive and significant effect on stock returns, the more effective the company is in managing its own capital, then the effort to increase stock returns can be realized. EPS has a positive and significant effect on stock returns, earnings per share contains important information to make predictions about dividends per share in the future. While NPM has a negative and significant effect on Stock Return, the high and low NPMs do not guarantee investors will buy these shares because NPM only makes a profit from each sale